Output gap and non-linear economic convergence - Beyaert, Arielle (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2014)
We apply unit root tests in a multivariate TAR model with bootstrapping simulations to assess the influence of short-run economic conditions on long-run economic convergence and to extract economic policy implications. We use two different groups of countries whose members share important business cycle characteristics over the period 1953–2010. We show that per capita income convergence is not uniform along the business cycle and our analysis reveals that, apart from growth-led actions and structural reforms to avoid the evolution towards different national stationary states – especially within the euro zone – short-run stabilisation policies are vividly advised to guarantee long-run economic convergence.